Uji Posisi Sumur Bor Terhadap Akuifer Menggunakan Metode Audio Magnetotelluric (ADMT) - Silalahi, Dio Carpry Gunawan; Simpen, I Nengah; Putra, I Ketut; Nurmalasari, Ni Putu Yuni; Suryatika, Ida Bagus Made; Kasmawan, I Gde Antha (Universitas Hamzanwadi, 2023)
Research has been carried out regarding the position test of the drilled well against the aquifer at the Jimbaran Unud Campus on May 12, 2023. The borehole test was carried out using the Audio Magnetotelluric (ADMT) method. To ensure that the water needs of all students at Udayana are met, it is necessary to conduct research on drilled wells at Udayana whether they are suitable for aquifer positions (groundwater). The purpose of this study was to determine the suitability of the position of the drilled well to the aquifer in the ground behind the UNUD Rectorate Building. Based on the interpretation of the results of the research conducted in this paper, the aquifer position sought on line 1 is at a distance of 0–9 m and 21–50 m at a depth of 100–200 m below the ground surface, while on line 2 it is at a distance of 7–50 m at a depth of 100–140 m. Because the position of the Udayana drilled well is at 22.2 m on line 1 and 26.7 m on line 2 with a depth of 74 m, the Udayana drilled well is not yet in the aquifer position sought in this study.